EVALUASI PEMBINAAN ATLETIK PASI PAMEKASAN - Yoyok Yulianto; Achmad Suparto; Dyas Andry Prasetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the long-distance running development program of the Indonesian Athletics Association (PASI) in Pamekasan Regency using the CIPP (Context, Input, Process, Product) evaluation model. This research employs a descriptive qualitative approach with a survey method. Data were collected through questionnaires, observations, and interviews involving one coach and seven long-distance athletes as respondents. The results of the context evaluation show that while the program has a strong foundation in terms of athlete motivation and organizational legality, it lacks a structured Long-Term Athlete Development (LTAD) roadmap. The input evaluation reveals that although the main track facilities are adequate, there is a significant shortage of sport science-based equipment and limited opportunities for coach competency development. In the process aspect, training is conducted routinely six times a week; however, the application of training periodization, including intensity and recovery management, is not yet systematic, and there is a lack of competitive exposure through try-outs. Consequently, the product evaluation indicates that while there is improvement in physical and technical skills, achievements remain inconsistent and are primarily limited to the district level, with less impact at the provincial level. The study concludes that to achieve consistent national-level performance, PASI Pamekasan must prioritize long-term strategic planning, integrate sport science into training, and enhance the frequency of competitive opportunities for its athletes.